The Role of Islamic Education in Sustainable Development and Ecology (SDGs) - Elisa Nur Maharani Husna; Wahid Adrian (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
This study explores the pivotal role of Islamic education in promoting sustainable development and ecological awareness in alignment with the Sustainable Development Goals (SDGs). Islamic teachings emphasize the principles of stewardship (khalifah fil-ardh), justice (adl), and balance (mizan), which resonate with contemporary sustainability concepts. By integrating these values into educational curricula, Islamic education can foster environmental ethics, responsible resource management, and social welfare. This paper highlights how Islamic educational institutions, including schools and universities, contribute to sustainability through curriculum design, green campus initiatives, and community engagement programs. Furthermore, the study examines the challenges and opportunities in embedding sustainability principles within Islamic pedagogy, emphasizing innovative approaches such as eco-pesantren, project-based learning, and digital platforms for environmental campaigns. The findings underscore that Islamic education not only supports moral and spiritual development but also plays a strategic role in shaping environmentally conscious generations who contribute to achieving global sustainability targets.